Pessoas com deficiência e políticas sociais em Portugal: Da caridade à cidadania social - Fernando Fontes (Revista Crítica de Ciências Sociais, 2009)
Based on an analysis of legislation affecting the disabled in Portugal during the last three decades, this article considers policies for the disabled developed between 1974 and 2008. In order to situate the analysis, the first part of the article identifies the underlying theoretical presuppositions, briefly reviewing the main theoretical-analytical models in this area of research. This is followed by a critical review of policies for the disabled in Portugal, identifying characteristics, trends and underlying ideologies. The final aim is to outline the characteristics of state actions in this area through an analysis of the implementation of policies for the disabled in Portugal.